The Role of Phospholipase C Signaling in Macrophage-Mediated Inflammatory Response - Liqian Zhu; Clinton Jones; Gaiping Zhang (Journal of Immunology Research)
Macrophages are crucial members of the mononuclear phagocyte system essential to protect the host from invading pathogens and are central to the inflammatory response with their ability to acquire specialized phenotypes of inflammatory (M1) and anti-inflammatory (M2) and to produce a pool of inflammatory mediators. Equipped with a broad range of receptors, such as Toll-like receptor 4 (TLR4), CD14, and Fc gamma receptors (FcγRs), macrophages can efficiently recognize and phagocytize invading pathogens and secrete cytokines by triggering various secondary signaling pathways. Phospholipase C (PLC) is a family of enzymes that hydrolyze phospholipids, the most significant of which is phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2]. Cleavage at the internal phosphate ester generates two second messengers, inositol 1,4,5-trisphosphate (IP3) and diacylglycerol (DAG), both of which mediate in diverse cellular functions including the inflammatory response. Recent studies have shown that some PLC isoforms are involved in multiple stages in TLR4-, CD14-, and FcγRs-mediated activation of nuclear factor kappa B (NF-κB), mitogen-activated protein kinase (MAPK), and interferon regulatory factors (IRFs), all of which are associated with the regulation of the inflammatory response. Therefore, secondary signaling by PLC is implicated in the pathogenesis of numerous inflammatory diseases. This review provides an overview of our current knowledge on how PLC signaling regulates the macrophage-mediated inflammatory response.